Patient experience and perceived acceptability of whole-body magnetic resonance imaging for staging colorectal and lung cancer compared with current staging scans: a qualitative study. Issue 9 (6th September 2017) - Evans, Ruth; Taylor, Stuart; Janes, Sam; Halligan, Steve; Morton, Alison; Navani, Neal; Oliver, Alf; Rockall, Andrea; Teague, Jonathan; Miles, Anne
Abstract : Objective: To describe the experience and acceptability of whole-body magnetic resonance imaging (WB-MRI) staging compared with standard scans among patients with highly suspected or known colorectal or lung cancer. Design: Qualitative study using one-to-one interviews with thematic analysis. Setting: Patients recruited from 10 hospitals in London, East and South East England between March 2013 and July 2014. Participants: 51 patients (31 male, age range 40–89 years), with varying levels of social deprivation, were recruited consecutively from two parallel clinical trials comparing the diagnostic accuracy and cost-effectiveness of WB-MRI with standard scans for staging colorectal and lung cancer ('Streamline-C' and 'Streamline-L'). WB-MRI was offered as an additional scan as part of the trials. Results: In general WB-MRI presented a greater challenge than standard scans, although all but four patients completed the WB-MRI. Key challenges were enclosed space, noise and scan duration; reduced patient tolerance was associated with claustrophobia, pulmonary symptoms and existing comorbidities. Coping strategies facilitated scan tolerance and were grouped into (1) those intended to help with physical and emotional challenges, and (2) those focused on motivation to complete the scan, for example focusing on health benefit. Our study suggests that good staff communication could reduce anxiety and boost coping strategies. Conclusions: Although WB-MRI was perceived as more challenging than standard scans, it was sufficiently acceptable and tolerated by most patients to potentially replace them if appropriate. Trial registration number: ISRCTN43958015 and ISRCTN50436483 .